2016
DOI: 10.3390/su8020176
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Competitiveness: Moving Towards Upstream Manufacturing in Specialized-Market-Based Clusters in the Chinese Toy Industry

Abstract: Western industrial cluster literature pays little attention to specialized markets (SMs) and the geographical agglomeration of distributors or sale agencies (SAs). This paper takes Linyin, Shandong, a famous commodity city in Northeastern China, as an example, to discuss the determinants that make SAs in SMs of the toy industry move towards upstream manufacturing. A structured questionnaire survey and subsequent interviews were carried out during 2011 and 2012 to collect data, and a Binary Logistic Regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…To determine the changing role of sales agencies (SAs) in the specialized market cluster (SMs), Zhu et al (2016) [13] used binary logistic regression, which starts with all variables in the regression equation, and then removes the independent variables that have no significant effect on the dependent variable according to the probability value of statistics derived from the maximum likelihood estimation .…”
Section: Methodologies Of Sustainability Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…To determine the changing role of sales agencies (SAs) in the specialized market cluster (SMs), Zhu et al (2016) [13] used binary logistic regression, which starts with all variables in the regression equation, and then removes the independent variables that have no significant effect on the dependent variable according to the probability value of statistics derived from the maximum likelihood estimation .…”
Section: Methodologies Of Sustainability Sciencementioning
confidence: 99%
“…Yiwu City in the Zhejiang Province and Linyi City in the Shandong Province are two typical examples of "commodity markets", situated in the north and south of China, respectively. Using Linyi City as the case study, Zhu et al (2016) [13] empirically tested the factors influencing the expansion of SAs from wholesale to manufacturing and on the scale of internal production with three kinds of determinants: individual motivations of entrepreneurial innovation, local agglomeration effects of SMs, and dynamic relationships with cross-cluster cooperation. The empirical results show that individual motivations of intra-firm coordination, regional inter-firm relationships, and cross-regional inter-firm relationships have a significant and positive impact on the upgrading of local industrial clusters to sustain local competitiveness.…”
Section: Important Issues For a Sustainable Asiamentioning
confidence: 99%
“…A growing body of literature has started to point out that China’s industrial clusters and specialized markets have increasingly confronted challenges from globalization and market openness (Bellandi & Lombardi, 2012; Zhu et al., 2016). Wei et al.…”
Section: China’s Specialized Markets In Evolution: a Literature Reviewmentioning
confidence: 99%
“…They may pay less attention to the building of local kinship‐based social networks (Li, Bathelt, & Wang, 2012) and become more outward‐looking and open in firm management and market strategy (Wei et al., 2007). Both aforementioned cases not only reshape the developmental trajectories of industrial clusters, but also impact their related specialized markets, in terms of the relations between market sellers and buyers and the configuration of supply chains and production networks (Zhu et al., 2016; Zhu & Pickles, 2015). These cases have shown that globalization can enable the openness and adaptability of specialized markets, which in turn may improve their technical efficiencies.…”
Section: China’s Specialized Markets In Evolution: a Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation